Case report: Infratentorial Embryonal Tumor with Abundant Neuropil and True Rosettes (ETANTR) in an 8-month-old Maine Coon - Foiani, Greta; Mandara, Maria Teresa; Carminato, Antonio; Melchiotti, Erica; Corrò, Michela; Vascellari, Marta (Frontiers in Veterinary Science, 2022)
An 8-month-old female Main Coon with a history of recurrent behavioral changes and anorexia was presented with sternal recumbency and depression. Within 5 days, the cat progressively worsened with symptoms of stupor and coma and was euthanized. At post-mortem examination, a solid, grayish infratentorial mass located in the midline rostrally to the cerebellum, was observed. Histologically, highly cellular clusters of small-to-medium undifferentiated cells were intermingled with paucicellular areas with fibrillary eosinophilic (neuropil-like) appearance. Numerous multilayered (ependymoblastic) true rosettes were present. The mitotic activity was frequent (up to 15 mitoses/HPF), involving both undifferentiated cells and rosettes. By immunohistochemistry (IHC), tumor cells were diffusely positive for vimentin, variably for synaptophysin, S-100, and NSE, and focally for NeuN; they were negative for GFAP and CK AE1/AE3. The histological and IHC aspects were consistent with an Embryonal Tumor with Abundant Neuropil and True Rosettes (ETANTR). Embryonal neoplasms of the central nervous system (CNS) are characterized by primitive undifferentiated cells, able to develop toward neuronal, glial, ependymal, and mesenchymal lines. Although extremely rare, juvenile embryonal tumors should be considered in the differentials of CNS disorders in young cats.